Peningkatan Kemampuan Berpikir Kritis dan Kreatif Siswa Kelas XI TITL di SMK N 1 Bukittinggi Melalui Problem Based Learning - Nurul Rahmawati; Habibullah (Journal of Electrical Vocational Education, 2026)
Abstract -This study was conducted to identify is improvement by students’ analytical thinking abilities and innovatice thinking skills to implementation of the Problemi Basedi Learningi (PBL) modeli ini thei Electricali Motor Installation subject at SMK Negeri 1 Bukittinggi. The study employed an research experiment using ai onei groupi pre-testi post-testi designi involvingi 36i students of class XI TITL 1. Data were gathered through pre-testsi, post-tests, andi classroom observations conducted during the learning process. The research instruments consisted of critical and creative thinking testsi andi observationi sheetsi. Datai werei analyzedi descriptively using SPSS through meani, standardi deviationi, andi N-Gaini calculations. The findings indicated an improvement in students’ abilitiesi afteri thei implementationi ofi thei Problemi Basedi Learningi modeli. Thei average pre-testi scorei ofi 48.06 increasedi toi 85.00 in thei post-testi, withi ani averagei N-Gaini scorei ofi 0.72 categorizedi asi highi. Observation resultsi showedi thati students’i criticali thinking skillsi reachedi ani averagei percentage ofi 82.22%, while creative thinking skills reached 82.47%, both categorized as good. During the learning process, students demonstrated better abilities in analyzing circuit disturbances, understanding relationships among components, and determining alternative solutions in electrical motor installation practices. The implementationi of Problemi Basedi Learningi encouraged students toi become more active andi analytical, creating a more contextual and problem-oriented learning environment.